Study of intestinal function in anorectal malformations: the role of Bowel management in quality of life - Lombardi, Laura; Garrisi, Elena; Ricco', Matteo; Marchesi, Federico; Casolari, Emilio; Gatti, Claudia; Del Rossi, Carmine G (Acta Biomedica Atenei Parmensis, 2016)
Purpose: We aimed at investigating bowel function in children and adolescents with anorectal malformations (ARMs) and assess their quality of life (QoL), in order to define a personal program of bowel management improving both clinical condition and self-confidence. Methods: A total of 55 patients treated for ARM by Posterior Sagittal Ano-Recto-Plasty (PSARP) from 2000 to 2014 were included into the study. The parents of 41 patients answered two telephone questionnaires about the parents’ self-efficacy and about QoL (GIQLI). A modified Peña score system was used to evaluate intestinal function. Twenty patients underwent anorectal manometry. After clinical assessment, all patients underwent an individual bowel management program. A median follow-up of 91.3 months was performed. Results: A significant inverse correlation was found between Peña score and GIQLI (r:-0.93, p<0.0001). Anorectal manometry paralleled the Peña score, showing an association between megarectum and constipation and soiling subdomains, especially in patients with higher ARM. Patients who carefully followed the bowel management program had significant improvements in both continence (0.93±1.1 vs 0.45±0.9, p=0.0005) and Peña score (4.6±3 vs 3.4±2.5, p<0.0001), which positively affected their self-confidence (100±26.6 vs 110±23, p<0.0001). Conclusions: The synergy of different scores and the evaluation of anorectal physiology proved useful to define the bowel management program, which seems to significantly impact both bowel function and QoL, with specific regard to soiling. Moreover, the Peña score might be also quantitatively used, as it parallels with both anorectal manometry and GIQLI, and the latter seems to be suitable for children. Further studies are required to confirm our findings.